The role of lncRNA SNHG14 in gastric cancer: enhancing tumor cell proliferation and migration, and mechanisms of CDH2 expression - Dai, Zhou-Tong; Wu, Yong-Lin; Xu, Tao; Li, Xing-Rui; Ji, Teng (Cell cycle (Georgetown, Tex.), 2023)
LncRNAs are a class of non-coding RNAs that play an important role in regulating gene expression. However, their specific molecular mechanisms in gastric carcinogenesis and metastasis need further exploration. TCGA data showed that the expression of MFGE8, which was closely related to survival, was significantly positively correlated with lncRNA SNHG14. And moreover, the results of high-throughput sequencing and qRT-PCR showed that lncRNA SNHG14 was significantly elevated in gastric cancer. Further, in vitro functional realization showed that lncRNA SNHG14 overexpression significantly increased gastric cancer's proliferation, invasion and migration. Animal experiments also showed that lncRNA SNHG14 overexpression promoted tumorigenesis and metastasis in vivo. Mechanistically, MFGE8 activates the expression of lncRNA SNHG14, which activates the cellular EMT by stabilizing CDH2. Our study suggests that lncRNA SNHG14 could be a potential target for gastric cancer therapy. Gastric cancer is one of the malignant tumors with a high incidence and high mortality rate worldwide. The current treatment modalities for gastric cancer are surgery, chemotherapy and targeted therapy. However, the 5-year survival rate of gastric cancer patients is still less than 30%. The main reason for the low survival rate of gastric cancer patients is that most cases are already at an advanced disease stage when first diagnosed, with tumor metastasis, tumor heterogeneity and resistance to radiotherapy. TCGA data showed that the expression of MFGE8, which was closely related to survival, was significantly positively correlated with lncRNA SNHG14.We found that lncRNA SNHG14 expression was significantly elevated in gastric cancer by high-throughput sequencing. It was further confirmed in vitro and in vivo that overexpression of lncRNA SNHG14 promoted the proliferation and migration ability of gastric cancer. Mechanistically, lncRNA SNHG14 played an oncogene role by promoting CDH2 expression to activate EMT in tumor cells.